Management of Strengthening Character Education Through Example and Characteristics - Endang Sulistyaniningsih (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the real situation/state of the management of character education through example and habituation in schools. The approach taken in this study uses a descriptive qualitative approach. Data collection techniques were carried out by observation, interviews, and documentation. Data analysis was carried out in three steps; data condensation, data presentation, and conclusion drawing. The conclusions of this study indicate: a) program planning to strengthen character education has several stages, namely observation, coordination, compiling work programs, program implementation, supervision, and evaluation, b) school principals are assisted by teachers, vice principal and related parties c) program implementation through four stages of activities, namely integration, exemplary, civilizing/ habituation , and cooperation with parents, d) direct program supervision process, e) program evaluation through the stages of evaluation preparation, data processing, and improvement. The findings in the field can be ascertained that the management of character education through exemplary and habituation is in accordance with the theories of several experts and the field in every process of activity in management to improve character education through exemplary and habituation continuously in one period according to the existing situation and conditions.